Ethnomedicinal and pharmacological perspectives on Alocasia cucullata: potential in cancer and immune modulation- A review - Kumar BS, Ashok; Bhargavi S, Bhargavi S; P M, Hema; Chaithanya A, Chaithanya A; Disha, N S (Journal of Neonatal Surgery, 2025)
Alocasia cucullata (Lour.) G. Don, commonly known as Chinese taro or Buddha's hand, is a fast-growing herbaceous plant in the Araceae family, renowned for its large, glossy leaves and often referred to as "Elephant’s ear." Widely recognized in traditional Chinese medicine, it is valued for its detoxifying, anti-inflammatory, and wound-healing properties. Recent pharmacological studies have revealed its significant anticancer potential, particularly against melanoma, gastric cancer, and breast cancer. The 50% ethanol extract (EAC) of A. cucullata exhibits strong antiproliferative effects against cancer cell lines such as B16-F10, A375, A2058 (melanoma), MGC-803 (gastric cancer), and SiHa (cervical cancer). Further analysis of the petroleum ether extract (EAC-PE) identified 43 bioactive compounds, while the n-BuOH fraction (EAC-B) induced cell cycle arrest and apoptosis, confirming its anticancer efficacy. Ten steroids and iridoids were isolated from A. cucullata tubers, including new compounds alocasgenin A and alocasgenoside B-C, alongside known compounds like tenacigenin B and marsdenoside A-B. These compounds demonstrated significant cytotoxic activity against MGC-803 and HT-29 tumor cell lines, with some exhibiting tyrosine kinase inhibition. Additionally, a water-soluble polysaccharide, ACP-1, isolated from the roots, showed immunostimulatory effects by enhancing RAW264.7 cell proliferation, phagocytosis, and cytokine secretion via the NF-κB pathway. Despite its therapeutic potential, A. cucullata remains understudied, necessitating further research to validate its traditional uses and explore its mechanisms of action. Its multifaceted bioactive properties position it as a promising candidate for modern therapeutic development, particularly in cancer treatment and immunomodulation. Bridging traditional knowledge with scientific investigation could unlock its full potential as a natural remedy